The beneficial effects of curcumin on aging and age-related diseases: from oxidative stress to antioxidant mechanisms, brain health and apoptosis - Ying He; Ying He; Yongqing Liu; Min Zhang (Frontiers in Aging Neuroscience)
Aging and age-related disease are among the most common and challenging issues worldwide. During the aging process, the accumulation of oxidative stress, DNA damage, telomere dysfunction, and other related changes lead to cellular dysfunction and the development of diseases such as neurodegenerative and cardiovascular conditions. Curcumin is a widely-used dietary supplement against various diseases such as cancer, diabetes, cardiovascular diseases and aging. This agent mediates its effects through several mechanisms, including the reduction of reactive oxygen species (ROS) and oxidative stress-induced damage, as well as the modulation of subcellular signaling pathways such as AMPK, AKT/mTOR, and NF-κB. These pathways are involved in cellular senescence and inflammation, and their modulation can improve cell function and help prevent disease. In cancer, Curcumin can induce apoptosis in a variety of different tumor cell lines. Curcumin also activates redox reactions within cells inducing ROS production that leads to the upregulation of apoptosis receptors on the tumor cell membrane. Curcumin can also upregulate the expression and activity of p53 that inhibits tumor cell proliferation and increases apoptosis. Furthermore, curcumin has a potent inhibitory effect on the activity of nuclear factor kappa B (NF-κB) and cyclooxygenase-2 (COX-2), which are involved in the overexpression of antiapoptosis genes such as Bcl-2. It can also attenuate the regulation of antiapoptosis phosphoinositide 3-kinases (PI3K) signaling and increase the expression of mitogen-activated protein kinases (MAPKs) to induce endogenous production of ROS. Therefore, herein, we aim to summarize how curcumin affect different epigenetic processes (such as apoptosis and oxidative stress) in order to change aging-related mechanisms. Furthermore, we discuss its roles in age-related diseases, such as Alzheimer, Parkinson, osteoporosis, and cardiovascular diseases.